Motivating Self-Efficacy in Diverse Biomedical Science Post-baccalaureate and Graduate Students Through Scientific Conference Implementation - Boehmer, Kasey R.; Boschen De Souza, Suelen Lucio; Doles, Jason D.; Lachman, Nirusha; Mays, Dennis; Hedin, Karen E.; Dornink, Cheryl A.; Maher, Louis J.; Lujan, J. Luis (Frontiers in Education, 2021)
Tactics to increase the number of underrepresented (UR) students in biomedical research PhD training programs have not yet translated to UR faculty numbers that reflect the diversity of the United States. Continued interventions are required to build skills beyond those that result in placement into a PhD program. We hypothesize that successful interventions must build skills that give UR students foundations for confident self-efficacy in leadership. We seek interventions that allow UR students to envision themselves as successful faculty. We posit that development of such skills is difficult in the classroom or laboratory alone. Therefore, novel interventions are required. As part of the NIH-funded Post-baccalaureate Research Education Program (PREP) and Initiative for Maximizing Student Development (IMSD) at the Mayo Clinic Graduate School of Biomedical Sciences, we designed and implemented a unique intervention to support development of student leadership skills: a biannual student-organized and student-led national research conference titled “Scientific Innovation Through Diverse Perspectives” (SITDP). This initiative is based on the concept that students who actively live out realistic roles as scientific leaders will be encouraged to persist to scientific leadership as faculty. Here we describe the motivation for, design of, and outcomes from, the first three pilot conferences of this series. We further discuss approaches needed to rigorously evaluate the effectiveness of such interventions in the future.